Evaluación ultrasonográfica de las gónadas del toro (Veterinary Science, 2017)
The exam andrologic of the bull is carried out through a series of studies that interrelated they allow to understand the integrity functional anátomo of the same one, each one of them sandal a specific area. The study protocol in an exploration of this type is continued through a methodical pursuit. The palpation, the measure of the escrotal perimeter and the evaluation of the semen provide important information to investigate the reproductive capacity, but tley cannot detect poteritial illnesses- The termography, the tonogriphy and tire tersticular biopsy ar not so accepted or they involve risks for the reproductive poteitial of animal. The ultrasound, as complementary method of diagnosis, allows to carry out an evaluation non invasive ofthe internal structuresofthe scrotum and testicle and the chances of diagnosis.
Keywords: Ultrasonography; testicles; Gonads